2016
DOI: 10.1590/s1677-5538.ibju.2014.0666
|View full text |Cite
|
Sign up to set email alerts
|

“Total reconstruction” of the urethrovesical anastomosis contributes to early urinary continence in laparoscopic radical prostatectomy

Abstract: Purpose:To demonstrate the effect of total reconstruction technique on postoperative urinary continence after laparoscopic radical prostatectomy (LRP).Material and Methods:LRP was performed using a standard urethrovesical anastomosis in 79 consecutive patients (Group-A) from June 2011 to October 2012, and a total reconstruction procedure in 82 consecutive patients (Group-B) from June 2012 to June 2013. The primary outcome measurement was urinary continence assessed at 1, 2, 4, 12, 24 and 52 weeks after cathete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 21 publications
(24 reference statements)
2
12
0
Order By: Relevance
“…A total of ten studies [ 10 , 18 23 , 25 27 ] comprising 12 trials reported the continence rate. For the study reporting the continence rate at 1 week, a total of five studies [ 18 , 19 , 22 , 25 , 26 ] comprising six trials were included; urinary continence was defined as 0 pads in two trials [ 19 , 22 ] and as 0 pads or 1 pad used for safety (0–1 for safety) in four trials [ 18 , 22 , 25 , 26 ]. For the study reporting the continence rate at 2 weeks, a total of four trials [ 19 , 20 , 25 , 27 ] were included; urinary continence was defined as 0 pads in three trials [ 19 , 20 , 27 ] and 0–1 for safety in one trial [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of ten studies [ 10 , 18 23 , 25 27 ] comprising 12 trials reported the continence rate. For the study reporting the continence rate at 1 week, a total of five studies [ 18 , 19 , 22 , 25 , 26 ] comprising six trials were included; urinary continence was defined as 0 pads in two trials [ 19 , 22 ] and as 0 pads or 1 pad used for safety (0–1 for safety) in four trials [ 18 , 22 , 25 , 26 ]. For the study reporting the continence rate at 2 weeks, a total of four trials [ 19 , 20 , 25 , 27 ] were included; urinary continence was defined as 0 pads in three trials [ 19 , 20 , 27 ] and 0–1 for safety in one trial [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the study reporting the continence rate at 4 weeks, a total of ten studies [ 10 , 18 23 , 25 27 ] comprising 12 trials were included; urinary continence was defined as 0 pads in five trials [ 19 , 20 , 22 , 23 , 27 ] and 0–1 for safety in seven trials [ 10 , 18 , 21 23 , 25 , 26 ]. For the study reporting the continence rate at 12 weeks, a total of six trials [ 10 , 18 – 20 , 25 , 26 ] were included; urinary continence was defined as 0 pads in two trials [ 19 , 20 ] and 0–1 for safety in four trials [ 10 , 18 , 25 , 26 ]. For the study reporting the continence rate at 24 weeks, a total of seven trials [ 10 , 18 – 20 , 25 27 ] were included; urinary continence was defined as 0 pads in three trials [ 19 , 20 , 27 ] and 0–1 for safety in four trials [ 10 , 18 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations